The woman’s occupation with HIV/aids syndrome: the daily routine facingthe (im)possibility of breastfeeding - Padoin, Stela Maris M; Souza, Ívis Emília L (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: the study question emerged due to experience in extension activities as a teaching practice and research in Nursing and in the acquaintance withwomen carrying HIV/aids. Objective: understanding the meaning of being a woman with HIV/aids in the daily routine in the (im)possibility of breastfeeding.Methods: it was a qualitative research in the phenomenological approach according to Martin Heidegger perspective. sixteen women were interviewed andtheir statements express what they feel, think, perceive, talk about, and how they relate themselves with others and with the subject researched in their dailyroutine. Results: the comprehensive analysis happened in the first methodic moment and allowed the construction of ten meaningful units. The interpretativeanalysis, the second methodic moment, demonstrated that the woman showed herself, in the way of being in the routine, in the impersonality, fearful andoccupied with her syndrome. Conclusion: in this study, the woman contributes showing the necessity of a care that makes possible getting out of “us” andbeing herself. It brings to light a care that makes recovery of the choice possible, that can give back the singularity of being, the one that helps to turn, the onethat sets free, the one that permits to put herself before a situation to can choose or decide for herself, the one that indicates the ante-position liberating.